Discovering ultrahigh loading of single-metal-atoms via surface tensile-strain for unprecedented urea electrolysis. Issue 12 (8th November 2021) - Kumar, Ashwani; Liu, Xinghui; Lee, Jinsun; Debnath, Bharati; Jadhav, Amol R.; Shao, Xiaodong; Bui, Viet Q.; Hwang, Yosep; Liu, Yang; Kim, Min Gyu; Lee, Hyoyoung
Abstract : Tensile-strain introduced on the surface of oxide support via liquid nitrogen quenching method stabilized ultra-high loading of single metal atom site for exceptional urea electrolysis. Abstract : Single-atom-catalysts (SACs) have recently gained significant attention in energy conversion/storage applications, while the low-loading amount due to their easy-to-migrate tendency causes a major bottleneck. For energy-saving H2 generation, replacing the sluggish oxygen evolution reaction with the thermodynamically favorable urea oxidation reaction (UOR) offers great promise, additionally mitigating the issue of urea-rich water contamination. However, the lack of efficient catalysts to overcome the intrinsically slow kinetics limits its scalable applications. Herein, we discover that incorporating tensile-strain on the surface of a Co3 O4 (strained-Co3 O4 ; S-Co3 O4 ) support by the liquid N2 -quenching method can significantly inhibit the migration tendency of Rh single-atoms (RhSA ), thereby stabilizing an ∼200% higher loading of RhSA sites (RhSA -S-Co3 O4 ; bulk loading ∼6.6 wt%/surface loading ∼11.6 wt%) compared to pristine-Co3 O4 (P-Co3 O4 ). Theoretical calculations revealed a significantly increased migration energy barrier of RhSA on the S-Co3 O4 surface than on P-Co3 O4, inhibiting their migration/agglomeration. Surprisingly, RhSA -S-Co3 O4 exhibited exceptional pH-universal UOR activity, requiring record-low working potentials and surpassing Pt/Rh-C, this was due to superior urea adsorption and stabilization of CO*/NH* intermediates, revealed by DFT simulations. Meanwhile, the assembled urea-electrolyzer delivered 10 mA cm −2 at only 1.33 V with robust stability in alkaline media. This work provides a general methodology towards high-loading SACs for scalable applications.